TRADISI “MAPPASIKARAWA” DALAM PERNIKAHAN ADAT BUGIS (Suatu Kajian Perspektif Hukum Islam) - Muh. Sudirman; Mustaring Mustaring (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
The article describes the Mappasikarāwa Tradition in the marriage of Bugis adat perspectives on Islamic law. From the results of the study with theological, philosophical, socilogical, anthropogical and juridical approaches, it can be understood that mappasikarāwa is a local knowledge of the Bugis community in marriage. This mappasikarāwa tradition has taken root in the procession of the Bugis marriage so that no marriage escapes the mappasikarāwa activities even though the implementation is different. Taradisi mappasikarāwa, by looking at the purpose and meaning of the tekadung in it generally corresponds to the principles of Islamic law, because; 1) Contain benefits and logics, 2) General applies to the community in a place or at least among the majority of the community, 3) It has been valid for a long time, not a new custom that will emerge later, 4) Not contrary to the syara 'argument or contradictory with the general principles of Islamic sharia. But the thing that needs to be revitalized is the malloangeng tradition shortly after the mappasikarawa tradition, where both partners compete to stand and step on each other. The myth contained in it is "who first stood up and stepped on his partner, then he is the one who has power in his household life going forward". Because this tradition is not in line with the purpose of marriage and the meaning and hope to be achieved at the event malloāngeng (bugis) which means that later this couple will always be united in going through their domestic life in the future